Punjab as the first Centre of Persian Literature in India - SYED ZAMIR UL HASSAN; ARSHAD MEHMOOD NASHAD (بازیافت, 2021)
In respect of literature, Punjab has been a fecund soil. It has played a dynamic role in disseminating Persian literature as it has done in all other languages which has enabled Persian literature to stand on par with Iranian literature. In comparison to Iraqi and Khurasani schools of thought the improvement of Hindi school of thought set in. Punjab plays a vital role in Persian literature. It gave out a spark which enlightened the whole of India with the scope of Persian literature. It is due to Punjab that the value and esteem of Persian literature in India because in the soil of Punjab grew up the towering writers like Naktai Lahori, Abul Farj Rooni Masood Saad Salman from whom the well-known writers like Anwar Zaheer Faryabi got the influence. The favorable clime of Punjab was conducive to the foundations of Persian in such a way that it sprouted and flourished to attain its new heights which was grafted into other languages. However, the actual impression is of Persian which shows its influence on Ghazal and other genres. And its originators are also the literary men in Punjab. The germination of Persian literature in this soil is the telling evidence of its fecundity. Not only did Punjab know the literary importance of Persian but it also made it billow into greatness and acquainted it with new tastes. It amalgamated the culture of Punjab with the civilization of India with such beauty as the turquoise in a ring doubles its grace. In respect of being the fundamental unit Hindustan Punjab is arguably the first center of Persian. In this study, analyzing the contribution of Punjab to Persian literature and Punjab as the first center of Persian literature in India are put forward.